Corrosion mechanisms in theory and practice / edited by P. Marcus and J. Oudar - Marcus, P.; Oudar, J. (Corrosion technology (New York, N.Y.), 1995)
This work offers in-depth discussions of advances in corrosion science and corrosion protection, providing key information necessary to understand and solve corrosion problems. It discusses microbial-induced and atmospheric corrosion, corrosion in nuclear systems and of microelectronics and magnetic storage devices, corrosion inhibition by organic molecules and the use of surface coatings for protection. This work is intended for chemical, materials, corrosion, mechanical, design, process, metallurgical, manufacturing and industrial engineers; materials scientists and surface chemists; applied physicists; and upper-level undergraduate and graduate students in these disciplines.